KONSELING ISLAMI DAN PENDIDIKAN MENTAL - Saiful Akhyar Lubis (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2010)
Abstract: Islamic Counseling and Mental Education. This paper analyzes the nature of Islamic counseling and its relation to mental education. It isundeniable that due to problems faced in this life man may be hindered from realizing his goals. In reality, however, not every individual is capable of solving his own problem but he needs assistance of others instead. In this context, this paper discusses an approach of what is the so called Islamic counseling. The writer tries to build a paradigm that, as a discipline of science as well as an approach, the writer argues that Islamic counseling is an endeavor to help solving the problem of individual based on the injunction of Islamic teaching. The writer argues that Islamic counseling provides support and assistance for individual to position himself as the servant of God, who is given capacity to solve his own problems independently and most importantly submit what would be the final outcomes to the Almighty God.Kata Kunci: konseling Islami, konselor, kesehatan mental